Preoperative leukocytosis is an independent risk factor for morbidity and survival after resection of colorectal liver metastases. Issue 10 (20th June 2022) - Schnitzler, Laura Julie; Oldhafer, Felix; Kulik, Ulf; Klempnauer, Jürgen; Reese, Tim; Oldhafer, Karl J.; Beetz, Oliver
Abstract: Background: Although surgical resection of colorectal liver metastases (CRLM) remains to be the only option for long term survival, traditional surgical concepts have been challenged by the introduction of the liver first approach or neoadjuvant chemotherapy in resectable CRLM and interventional therapies. The aim of this study was to identify prognostic factors for postoperative morbidity and survival and to externally evaluate the recently introduced resection severity index (RSI), in order to optimize patient selection and treatment strategies. Methods: This is a retrospective single centre analysis of 213 patients undergoing surgery for CRLM in curative intent between January 2010 and December 2018. Results: Median follow up after liver resection was 28.56 (0.01–111.46) months. Severe postoperative complications (Clavien‐Dindo ≥ IIIa) were observed in 46 (21.6%) cases. Preoperative leukocytosis (OR: 3.114, CI‐95%: 1.089–8.901; p  = 0.034) and operation time in minutes (OR: 1.007, CI‐95%: 1.002–1.011; p  = 0.002) were determined as independent risk factors. Overall survival (OS) was 46.68 months with a 5‐year survival rate of 40.5%. Independent prognostic factors were preoperative leukocytosis (HR: 2.358, CI‐95%: 1.170–4.752; p  = 0.016), major hepatectomy (HR: 1.741, CI‐95%: 1.098–2.759; p  = 0.018) and low grading of the primary intestinal tumour (HR: 0.392, CI‐95%: 0.231–0.667; p  < 0.001). The RSI (ASAT (U/l) divided by Quick (%) multiplied by the extent of liver resection in points) was identified as independent risk factor for OS only in patients without neoadjuvant chemotherapy. Conclusions: Detection of leukocytosis in patients prior resection of CRLM was associated with increased postoperative morbidity and decreased OS and could therefore prove valuable for perioperative risk stratification. Abstract : The detection of preoperative leukocytosis in patients undergoing resection for colorectal liver metastases could prove valuable for future perioperative risk stratification, as we observed association with increased postoperative morbidity and decreased overall survival.